3D printing of bioinspired topographically oriented surfaces with frictional anisotropy for directional driving. (April 2019) - Ji, Zhongying; Yan, Changyou; Ma, Shuanhong; Gorb, Stanislav; Jia, Xin; Yu, Bo; Wang, Xiaolong; Zhou, Feng
Abstract: Friction anisotropic surfaces with oriented micro-/nanostructures are widely spread in biological systems and play important roles for effective locomotion or transporting items. Herein, 3D printing was employed to build the structures mimicking the hook-like features of the Filefish skin surface having typical interfacial anisotropy. Friction tests revealed that the surface with flexible supporting layer (similar to biological prototype) had low friction force in both sliding directions, but exhibited larger frictional anisotropy in comparison with the surface with rigid supporting layer. Interestingly, the anisotropic friction of the 3D printed surfaces led to directional driving when oscillated in contact with other surfaces. This effect makes biomimetic surfaces with oriented surface structures promising candidates for directional actuation, intelligent sensors and specific tribological applications. Highlights: 3D printing is employed to build friction anisotropic surfaces with biomimetic topographic-orientation microstructures. The structured surfaces with flexible PDMS substrate reveal lower friction force, but larger frictional anisotropy. Friction behavior of the hard-on-soft biomimetic surface is much similar to that of the natural fish surface. Effects affecting frictional anisotropy are systematically investigated in detail.